Ultrasonic Haptic Devices: Ultrasonic Noise Assessment - MORZYŃSKI, Leszek; PODLEŚNA, Marlena; SZCZEPAŃSKI, Grzegorz; WŁUDARCZYK, Anna (Archives of Acoustics, 2024)
Ultrasonic haptic technology is one of the more interesting novel technologies being intensively developed in recent years. Such technology has a number of undoubted advantages and potential applications, but it can also be a source of ultrasonic noise. Pursuant to the provisions of the labor law, ultrasonic noise at a high sound pressure level can be a harmful factor for human health. The article presents the results of the assessment of ultrasonic noise emitted by an ultrasonic haptic device and the assessment of exposure to noise of a person using the device. The tests were carried out using one of the haptic devices readily available on the market. Ultrasonic noise emission tests were carried out around the device, at selected points placed on the surface of a hemisphere of a radius of 0.5 m, for various haptic objects. The analyzed parameter was the equivalent sound pressure level in the 1/3 octave band with a center frequency of 40 kHz. Variable sound pressure levels ranged from 96 dB to 137 dB. Noise exposure tests were carried out both using the KEMAR measurement dummy and with test participants of different heights. In most cases, the sound pressure level exceeded 110 dB, and in the worst case it exceeded 131 dB. Comparison of the results of ultrasonic noise assessments with the permissible values of this noise in the working environment shows that in the case of prolonged or improper use of the device, the permissible values may be exceeded.